Arbuscular mycorrhizal and dark septate endophyte fungal association in some vegetable and staple food crops of Manipur, North eastern India - R.R. PANDEY*, K. SURENDIRAKUMAR and (Indian Phytopathology, 2016)
Roots and rhizosphere soil samples of two vegetable crops viz. Naga King Chili (Capsicum chinense Jacq.), cowpea (Vigna unguiculata (L.) Walp.), and an indigenous rice (Oriza sativa L.) cultivar i.e. Phourel angouba, were examined for the occurrence of arbuscular mycorrhizal (AM) and dark septate endophyte (DSE) fungi during the fruiting stage. This study provides the first comprehensive report on these fungal associations in C. chinense and O. sativa AM fungal spore density was highest in C. chinense rhizosphere. A total of 14 AM fungal morphotypes were isolated from different crop soils. Intensity of AM and DSE fungal root colonization and distribution of their structures varied significantly with the host species. Arum- and Paris- types of AM morphology were observed in the test plants. Total root length with AM colonization (%RLTC) was highest in C. chinense, whereas that of DSE colonization (%DSTC) was maximum in O. sativa cv.